Effect of additives on mycelial growth and fructification of Pleurotus squarrosulus (Polyporales: Polyporaceae) - Kadiri, Mukaila (1994)
The effects of dungs (cow, horse. poultry), yam peels, rice bran, chaff (Sorghum, maize) and several sugars on mycelial growth and fructification of Pleurolus squarrosulus (Mant.). Singer were investigated. The concentrations were 5%, 10% and 15% (for sugars: 1%,3% and 5%). The substrate raw materials were maize and rice straw and cotton waste (substrates without the additives used as controls). Optirnum mycelial growth was obtained with 10% rice bran, or Sorghum or maize chaff, 5% dung (any) and 5% sugars. Mycelial growth increased with concentratian of the sugars and decreased with dung and yam peel concentration. All additives accelerated primordial formation and increased the number of fruitbodies. Rice bran was the best in promoting fructificaction, followed by glucose and fructase; Sorghum chaff was the poorest. Sugars promoted fructification more han dungs or chaffs bot less than rice bran.